Exploratory study of a crisis commander’s perspectives on the role and value of public relations in crisis management - Mat Tazin, Saidathul Nizah; Kaur, Kiranjit (2017)
This is an exploratory study into understanding the dominant coalition perspectives on role and values of public relations in crisis management in an energy company in Malaysia. In this study, the senior public relations of the energy company reports directly to the crisis commander (CC) in times of crisis thus, the CC was chosen as a sample where an in-depth interview was conducted. Notably, the CC perceptions represents the dominant coalition with the power to shape organisation policies and provide directions to public relations practice in managing media and communication in crisis management.Theory of excellence within the outlook of public relations empowerment was examined.The findings of this study have significantly confirmed that the patterns of the CC perceptions on role and values of public relations in crisis management are similar to other dominant coalition literature across the globe.This phenomenon needs changes to drive public relations to strive harder to be a problem solver and a strategic thinker in crisis management.This study is a significant attempt to understand the perception of the dominant coalition on public relations in crisis management and can be replicated in other sectors in Malaysia.